2018
DOI: 10.3847/1538-3881/aac3d2
|View full text |Cite
|
Sign up to set email alerts
|

Basalt or Not? Near-infrared Spectra, Surface Mineralogical Estimates, and Meteorite Analogs for 33 Vp-type Asteroids

Abstract: Investigations of the main asteroid belt and efforts to constrain that population's physical characteristics involve the daunting task of studying hundreds of thousands of small bodies. Taxonomic systems are routinely employed to study the large-scale nature of the asteroid belt because they utilize common observational parameters, but asteroid taxonomies only define broadly observable properties and are not compositionally diagnostic. This work builds upon the results of work by Hardersen et al., which has th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 65 publications
3
34
0
Order By: Relevance
“…For the regression line for the temperature-corrected V-type band centers to overlap the HED regression line, the Band II centers for the NEAs would need to be corrected on average by~0.02 μm. We note that Hardersen et al (2018) found a much better correlation between the trend for HEDs and the trend for inner-belt V-types after a temperature correction in a plot of Band II versus Band I centers.…”
Section: Journal Of Geophysical Research: Planetsmentioning
confidence: 55%
See 1 more Smart Citation
“…For the regression line for the temperature-corrected V-type band centers to overlap the HED regression line, the Band II centers for the NEAs would need to be corrected on average by~0.02 μm. We note that Hardersen et al (2018) found a much better correlation between the trend for HEDs and the trend for inner-belt V-types after a temperature correction in a plot of Band II versus Band I centers.…”
Section: Journal Of Geophysical Research: Planetsmentioning
confidence: 55%
“…However, some HEDs have distinctly different oxygen isotope values from typical HED values (e.g., Benedix et al, ; Scott et al, ) implying more than one Vesta‐like asteroid formed in the solar system. Hardersen et al () has determined the pyroxene mineralogies of approximately 30 V‐type asteroids in the inner and outer belt to test their mineralogical relationship with Vesta.…”
Section: Introductionmentioning
confidence: 99%
“…5), instead they are only weakly correlated at 85% significance, and B1 and BAR to show essentially no correlation (e.g. Hardersen et al 2018). We note that while these correlations are statistically significant, the changes, particularly in the band centers, are quite small and thus would have minor compositional implications.…”
Section: Spectral Analysismentioning
confidence: 64%
“…They are called V-type candidates (in order to avoid the confusions with the spectrally classified V-types). The follow-up spectroscopic surveys confirmed them with a higher probability, in the range of 80 -90 % (Moskovitz et al 2010;de Sanctis et al 2011;Hardersen et al 2014Hardersen et al , 2015Migliorini et al 2017Migliorini et al , 2018Hardersen et al 2018;Medeiros et al 2019). Based on the V-type candidates obtained from the Sloan Digital Sky Survey (SDSS) spectrophotometric data, Moskovitz et al (2008) provides a first estimation of the unbiased size-frequency and semi-major axis distribution of basaltic objects.…”
Section: Introductionmentioning
confidence: 89%